Color stability assessment of two different composite resins with variable immersion time using various beverages: An In vitro study - M Senthil Kumar; R Ajay; S A Miskeen Sahib; M Chittrarasu; M Navarasu; N Ragavendran; Omar Farooq Burhanuddin Mohammed (Wolters Kluwer Medknow Publications, 2017)
Purpose of the Study: The aim of the study was to evaluate the difference in the color of microhybrid (MH) and nanofilled (NF) composite resins after 24 and 48 h in beverages such as red wine (RW), Coca-Cola, and distilled water. The specific objective of this study was to investigate the cumulative effect of the colorant solutions on the dental composites. Materials and Methods: MH and NF composite resins (A2 shade) were used in this current study. Sixty disk-shaped material specimens (10 mm in diameter × 2 mm in thickness) were prepared using a fiber mold (ring), with the desired dimensions. The specimen surfaces were polished using super-snap polishing system. Sixty specimens were divided into two groups of 30 each (Group I: MH resin composite; Group II: NF resin composite). Both the groups divided into six subgroups (Subgroup I: RW for 24 h [RW-24]; Subgroup II: RW for 48 h; Subgroup III: Coca-Cola for 24 h [CC-24]; Subgroup IV: Coca-Cola for 48 h [CC-48]; Subgroup V: Distilled water for 24 h [DW-24]; Subgroup VI: Distilled water for 48 h [DW-48]). All the samples were immersed in respective drinks for a period of 24 h, and color differences were measured using ultraviolet spectrophotometer. Once again, all the samples were immersed for another 24 h in the same drinks. After 48 h, the color change of the samples was measured. Measurements were made according to the CIE L × a × b × color space relative to the CIE standard illuminant D65. The color changes of the specimens were evaluated using the following formula: [INSIDE:1]Statistical analysis was performed. The data were analyzed using the one-way ANOVA and t-test at a significance level of 0.05. Conclusion: Color stability of MH composite resin was found to be inferior than the NF resin composite irrespective of immersion medium and time. In RW, the color change observed was maximum for both composite resins followed by Coca-Cola. Immersing the resin composites in distilled water for 24 and 48 h had negligible color change. A 48-h immersion of both composite resins in all three immersion mediums showed greater color change than 24 h immersion.